The Effectiveness of Healthcare Operations for Dependent Elderly People of Care Giver Kham Ta Kla District Sakon Nakhon Province - Promkawong , Wangai (Medical Journal of Sakon Nakhon Hospital, 2024)
This research is a cross-sectional analytical study using the CIPP Model evaluation framework, which includes context, input, process, and product evaluation. The sample consisted of 74 Care Givers in Kham Ta Kla District, selected through simple random sampling. Data was collected using questionnaires from September to October 2024. The data was analyzed using descriptive statistics including frequency, mean, percentage, standard deviation, and inferential statistics including Pearson’s correlation coefficient and stepwise multiple regression analysis to predict factors affecting the effectiveness of elderly care performance among caregivers for dependent elderly. The results showed that caregivers had good overall knowledge scores for dependent elderly care ( = 14.20, S.D. = 2.48) and good overall skill scores for dependent elderly care ( = 59.91, S.D. = 6.81). The social support factors were at a good level overall ( = 106.62, S.D. = 6.65). The knowledge (r = 0.246, p = 0.036), community acceptance (r = 0.430, p < 0.001), support from sub-district health promoting hospitals (r = 0.478, p < 0.001), support from local administrative organizations (r = 0.252, p = 0.032), and support from network hospitals (r = 0.424, p < 0.001) were significantly correlated with the overall effectiveness of dependent elderly care performance of Care Givers at the 0.05 level. Furthermore, support from sub-district health promoting hospitals, community acceptance, support from network hospitals, and knowledge collectively predicted 61.7% of the variance in Care Givers’ effectiveness in providing care for dependent elderly (R2 = 0.617, p < 0.05). This study demonstrates that Care Givers who receive support from sub-district health promoting hospitals, community acceptance, support from network hospitals, and possess knowledge show improved effectiveness in providing care for dependent elderly.